Comparison of Self-Assessment and Students’ Perspective Regarding Teaching Effectiveness of Medical Teachers (Medical Forum Monthly, 2021)
Objective: The objective of this study is to compare the teaching effectiveness of medical teachers from a teacher’s self-evaluation perspective and student’s evaluation of teaching effectiveness.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Operative Dentistry, Foundation University College of Dentistry and Hospital, Islamabad for one-month March to April 2021.Materials and Methods: This study was conducted in Foundation University College of dentistry FUCD of Fauji Foundation University. This study was a cross-sectional study of 1-month duration. 200 dental students from all four years of BDS and 20 medical teachers were selected through non-purposive convenience sampling. Teaching effectiveness was assessed first from 20 teachers and then similar teachers were evaluated by 200 dental students (10 students evaluated 1 teacher). For self- evaluation of teaching effectiveness, the validated tool “Self- assessment Instrument for teacher evaluation (SITE)” was used and filled by teachers. For student’s evaluation of teaching effectiveness, the tool “Evaluation of teaching performance (CEID)” was used and filled by 200 students from all 4 years of BDS.Results: Teachers rated their teaching more eﬀective with a mean score (M=120) than students. The result was signiﬁcant statistically. With respect to 60% cut-off score, all the teachers (100%) rated themselves as effective teachers.Conclusion: Teachers think that their teaching effectiveness is more as compared to students perception evident by results. This reflects evaluation and communication gap between teachers and students. Therefore, there is a need of development of evaluation system with evaluation tool of 360-degree vision either six monthly or yearly in which students should be the major stakeholders for teachers evaluation. Other than that Faculty development program and workshops should be made part of curriculum.